Implementasi Strategi Contextual Teaching And Learning (CTL) Dalam Pembentukan Kedisiplinan Peserta Didik Pada Mata Pelajaran Pendidikan Agama Islam - Marwah Marwah; Abdul Halik; Musyarif Musyarif (Journal on Education, 2024)
This research discusses the implementation of Contextual Teaching and Learning (CTL) strategies in forming student discipline in Islamic Religious Education subjects. Implementation of the Contextual Teaching and Learning (CTL) strategy in forming student discipline in Islamic Religious Education subjects can be done with an approach that integrates real life contexts with learning Islamic religious concepts. By applying this strategy consistently, students can form strong discipline, which will support ther academic success and overall character development